Penawaran, Permintaan dan Konsumsi Produk Peternakan di Indonesia - Tjeppy D. Soedjana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1997)
Supply of livestock products from 1969 to 1994 indicated that meat has been the most dominating commodity than milk and eggs due to its variability of meat producing species and of the accessibility product by consumers. However, beef and steers imports increases each year from 12,000 head in 1991 by more than 90 percent per year. Egg production from all poultry species also increasing each year that its target in production has been achieved, hence, it is indicating that national poultry industry has been successfully implemented through commercial poultry industry as well as intensification programs for both native chickens and ducks particularly in the Presidential Instruction (Inpres) program for village improvements that directly created new investments for poultry in the villages. Milk production has been contributing no more than 35 percent to the total national milk demand, even the domestic milk productivity increases and hence milk imports continues to increase in volumes. The demand for beef and foultry meat imply is elasticity to price change paricularly for low income group and those of rural consumers. Broiler meat tends to have substitute roles with beef and complementer in nature with milk and milk products. Percapita consumption of livestock product alwalys related with consumer's income and historically the per capita consumption of meat, milk and eggs are improved every yar and for some reasons, certain species have been achieved beyond the target. During 1998 - 2003 it is estimated that meat production may bae able to grow by 5.37 percent per year from 1.7 milion tons in 1998 to 2,5 milion tons in 2003, compared to Pelita VI (1994-1998) which grew by 5,5 percent. Eggs production is expected to grow by 3.4 percent per year from 0.7 milion tons in 1998 to 0.9 percent in 2003 while in Pelita VI it wasa able to grow by 5.4 percent. Domestic milk production which was growing by 5.7 percent in Pelita VI, is projected to grow only by 2.5 percent per year, from 0.7 milion tons in 1998 to 0.56 million tons in 2003. Only meat production will be able to meat the demand using low economic growth of 3 percent annually, and that with assumption of hight economic grow of 6 percent per year there will be no supply or production of livestock commodities are able to meets its respective demans by the consumers. Therefor, efforts to ward improving local species in terms of their productivity in the long run have to be critically anticipated due to growing population and increasing welfare and income of Indonesian people.